434 Are the complications after lymph node groin dissection for the treatment of vulvar cancer correlated to drainage system? Comparison of siliconized penrose and porto VAC. (18th September 2019) - Dias-, A; Sartor Faria, MB; Cesar Signorini Filho, R; Truffa Kleine, R; Luis Costa Ennes, A; Pizzinatto Micelli, L; Souza Sandon, L; Wagner, M; Vieira Luna Mayerhoff, E; Paula Carvalho, J; Chada Baracat, E
Abstract : Objectives: The aim of this retrospective case control study is to compare the efficacy of vacuum accessorized drain system to the siliconized penroze drain for the groin. Methods: From 2011 to 2019, 66 of 120 patient from the Outpatient Clinic of Gynecological Oncology Cancer Institute (ICESP) with advanced vulvar cancer were submitted to groin lymphadenectomy. The patients were divided in two groups: a) siliconized penrose drain (case group), b) vaccum accessorized 4, 8 mm drain (control group). Each patient had the groin dissection and the drain systen exteriorized by a medial common incision on the pubis, linked to a colostomy bag. The efficacy of the drainage was determinate by the following variables: infection, dehiscence, bleeding, lymphocele and day of hospitalization. Results: There was no diference in total number of complications (31, 4% case vs 35, 4% control). Specific complications such infection (28, 6% case vs 9, 67% control), bleeding (0% case vs 3, 22% control), dehiscence (0% case vs 6, 45%control) and lymphocele (8, 5% case vs 19, 3% control) were also not statistically diferent. Rehospitalization, however, was signficantly diferent (0% case vs 22, 5% control, p<0.0001), as tumor size (39, 46 mm case vs 50, 34mm control, p=0.01). Conclusions: Although the complications rate were similar, vacuum accessorized drain systen presented more index of lymphoceles, dehiscence and hospitalization days than siliconized penrose drain.